Сучасні інструменти автоматизованої конверсії відеоконтенту в статичні зображення та текстову інформацію - Левикін, І. В.; Шимко, Д. І. (ТОВ «Видавництво Ліра-К», 2025)
This paper explores the conversion of video content into text and images using AI tools, focusing on preserving the visual and auditory context. It examines current transcription services, such as OpenAI’s Whisper, and discusses the challenges of maintaining content accuracy while automating the conversion process.
Keywords: конверсія; відеоконтент